Quantitative progradation dynamics and stratigraphic architecture of ancient shallow-marine clinoform sets: a new method and its application to the Upper Jurassic Sognefjord Formation, Troll Field, offshore Norway - Patruno,S; Hampson,GJ; Jackson,CAL; Whipp,PS (Basin Research, 2014)
This paper presents a new numerical inversion method to estimate progradation rates in ancient shallow-marine clinoform sets, which is then used to refine the tectono-stratigraphic and depositional model for the Upper Jurassic Sognefjord Formation reservoir in the super-giant Troll Field, offshore Norway. The Sognefjord Formation is a 10-200 m thick, coarse-grained clastic wedge, that was deposited in ca. 6 Myr by a fully marine, westward-prograding, subaqueous delta system sourced from the Norwegian mainland. The formation comprises four, 10-60 m thick, westerly-dipping, regressive clinoform sets, which are mapped for several tens of kilometres along strike. Near-horizontal trajectories are observed in each clinoform set, and the sets are stacked vertically. Clinoform age and progradation rates are constrained by: (1) regionally correlatable bioevents, tied to seismically mapped clinoforms and clinoform-set boundaries that intersect wells, (2) exponential age-depth interpolations between bioevent-dated surfaces and a distinctive foreset-to-bottomset facies transition within each well, and (3) distances between wells along seismic transects that are oriented perpendicular to the clinoform strike and tied to well-based stratigraphic correlations. Our results indicate a fall in progradation rate (from 170-500 to 10-65 km/Myr) and net sediment flux (from 6-14 to ≤1 km2/Myr) westwards towards the basin, which is synchronous with an overall rise in sediment accumulation rate (from 7-16 to 26-102 m/Myr). These variations are attributed to progradation of the subaqueous delta into progressively deeper waters, and a concomitant increase in the strength of along-shore currents that transported sediment out of the study area. Local spatial and temporal deviations from these overall trends are interpreted to reflect a subtle structural control on sedimentation. This method provides a tool to improve the predictive potential of sequence stratigraphic and clinoform trajectory